2015
DOI: 10.1080/23120053.2015.1074443
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal septicaemia: prevalence and antimicrobial susceptibility patterns of common pathogens at Princess Marina Hospital, Botswana

Abstract: Background: Septicaemia is the third most common cause of neonatal death after prematurity and birth asphyxia. The prevalence of neonatal sepsis and the spectrum of causative microorganisms fluctuates over time, thus facility-specific surveillance of neonatal bloodstream infections is important. Increasing levels of antimicrobial resistance documented worldwide, necessitate regular monitoring of institutional resistance patterns to ensure appropriate and effective empirical antimicrobial therapy. Method:The la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 24 publications
(43 reference statements)
5
24
1
Order By: Relevance
“…Pooled prevalence of non-susceptibility of E coli isolates to ampicillin 63,74,79,84,86,88,98,106,112,113,118,124,125,127,132,135 was 89% (95% CI 77-97) and was 47% (25-69) to gentamicin. 63,74,79,84,86,88,91,97,98,106,126,127,113,118,132,135,[123][124][125] A third of E coli isolates were resistant to ceftriaxone. 74,79,84,86,88,97,98,106,112,113,118,122,133 The reported prevalence of ESBL-producing E coli isolates ranged from 12% (7/58) in South Africa 24 to 46% (10/22) in Tanzania.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pooled prevalence of non-susceptibility of E coli isolates to ampicillin 63,74,79,84,86,88,98,106,112,113,118,124,125,127,132,135 was 89% (95% CI 77-97) and was 47% (25-69) to gentamicin. 63,74,79,84,86,88,91,97,98,106,126,127,113,118,132,135,[123][124][125] A third of E coli isolates were resistant to ceftriaxone. 74,79,84,86,88,97,98,106,112,113,118,122,133 The reported prevalence of ESBL-producing E coli isolates ranged from 12% (7/58) in South Africa 24 to 46% (10/22) in Tanzania.…”
Section: Resultsmentioning
confidence: 99%
“…However, among the studies that reported CoNS as a pathogen, few provided a rationale for identifying the clinical significance of the infection. 24,36,122,131,132,135 Four studies 36,60,107,121 cited laboratory quality control measures, and only one study 107 sent samples to an external laboratory for confirmation. (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and Escherichia coli 10% (8-13; table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations